La1−xSrxMnO3 Thin Films on Silicon Prepared by Magnetron Sputtering: Optimization of the Film Structure and Magnetic Properties by Postdeposition Annealing. Issue 12 (1st October 2021) - Monecke, Manuel; Richter, Peter; Bülz, Daniel; Robaschik, Peter; Zahn, Dietrich R.T.; Salvan, Georgeta
Abstract : Herein, a systematic study of postdeposition annealing for La1− x Sr x MnO3 (LSMO) films regarding their structural, electronic, (magneto‐)optical, and magnetic properties is presented. The samples are prepared by magnetron sputtering at room temperature on silicon (111) substrates with native oxide and are annealed in ambient atmosphere for 12 h in a temperature range from 600 to 875 °C. The stoichiometry of the films is investigated by X‐ray photoelectron spectroscopy (XPS), and Raman spectroscopy is utilized to investigate the vibrational modes of the films. The diagonal and off‐diagonal components of the dielectric tensor are investigated by variable‐angle spectroscopic ellipsometry and magneto‐optic Kerr effect (MOKE) spectroscopy, respectively. The remanence and the coercive field of the layers are characterized by superconducting quantum interference device (SQUID) magnetometry. The magnetic properties are found to improve with increasing annealing temperature up to 850 °C, whereas the resistivity remains within a range between 0.5 and 2 Ωcm. The highest suitable annealing temperature for applications is, however, 775 °C due to the formation of a diffusion layer between LSMO and silicon oxide at higher temperatures. Abstract : The structural, electronic, (magneto‐)optical, and magnetic properties of La1− x Sr x MnO3 (LSMO) films prepared by magnetron sputtering at room temperature on Si(111) substrates are characterized before and after postdeposition annealing in ambient atmosphere. The highest suitable annealing temperature for applications is found to be 775 °C due to the formation of a diffusion layer between LSMO and silicon oxide at higher temperatures.